Fragment‐Based Drug Discovery in the Bromodomain and Extra‐Terminal Domain Family. Issue 8 (17th July 2017) - Radwan, Mostafa; Serya, Rabah
Abstract : Bromodomain and extra‐terminal domain (BET) inhibition has emerged recently as a potential therapeutic target for the treatment of many human disorders such as atherosclerosis, inflammatory disorders, chronic obstructive pulmonary disease (COPD), some viral infections, and cancer. Since the discovery of the two potent inhibitors, I‐BET762 and JQ1, different research groups have used different techniques to develop novel potent and selective inhibitors. In this review, we will be concerned with the trials that used fragment‐based drug discovery (FBDD) approaches to discover or optimize BET inhibitors, also showing fragments that can be further optimized in future projects to reach novel potent BET inhibitors. Abstract : The bromodomain is one of the epigenetic readers that recognizes and binds to acetylated lysine. Since the discovery of potent inhibitors for the bromodomain and extra‐terminal domain (BET) family, this protein–protein interaction has been the therapeutic target for human disorders like viral infections, atherosclerosis, and cancer. Using fragments, medicinal chemists developed many selective BET inhibitors with better ligand efficiency and pharmacokinetic properties.